Production of Feed Crops for Local Dairy Goats Using an Integrated Farming System - Tri Eko Susilorini; Kuswati Kuswati; Rini Dwi Wahyuni; Puguh Surjowardojo; Suyadi Suyadi (AGRIVITA, Journal of Agricultural Science, 2022)
This investigation aimed to identify the production and composition of crops as feed, classify the types of integrated farming in different locations, and compare dairy goats based on their morphometric characteristics. The data used were collected from July to November, 2021 in the Malang, Lumajang, and Bangkalan regencies of Indonesia, via a survey and direct observations. Descriptive, multivariate, and variance analyses were adopted using RStudio to analyze the collected data. In Malang and Lumajang, farmers adopted agroforestry, alley cropping, and cover crops as the main types of integrated farming. The integrated farming adopted by the farmers in Malang, Bangkalan, and Lumajang helped to explain the differences in forage crops. Calliandra calothyrsus, Indigofera zollingeriana, and Thitonia diversifolia are non-grasses having high levels of average production. In Lumajang, farmers provided only a few combinations with Calliandra which was the most intensively grown crop. In Malang, six crops were combined for the dairy goat feed. Pennisetum purpureum was the crop most intensely grown to feed the PE (Etawa crossbred). In Bangkalan, Pote-Arosbaya goats were fed a combination of eight crops. Moringa oleifera, Bambusa sp., Artocarpus heterophyllus, and natural grasses were the most popular feed crops. In Malang and Lumajang, the PE Singosari and Senduro goats had a high degree of similarity based on their morphometric characteristics, respectively.